Improved self-tuning PID control based on pattern recognition - Chengli Su; Guanghui Zhang; Bin Liu (2010 International Conference on Information, Networking and Automation (ICINA), 2010)
To solve the shortcomings of traditional PID controller in dealing with disturbance rejection and robustness a new self-tuning PID-based algorithm for pattern recognition is proposed. In the algorithm, the parameter tuning rules of the PID controller are innovated, and the specific formula for setting the rules is put forward. In order to achieve the water tank level control algorithm in the application of laboratory, using OPC technology to achieve the MATLAB software and data configuration software MCGS real-time interaction. Experimental results show that the given tuning rules in MATLAB simulation and tank level control applications take the effect of good tuning. The control performance of the proposed self-tuning PID control method is superior to that of traditional PID method.